The complete chloroplast genome of a centennial olive tree (Olea europaea, Oleaceae) from the southern Peruvian coast - Saldaña, Carla L.; Chura Llanos, Luz S.; Estrada Cañari, Richard; Fernandez Huaytalla, Elizabeth; Zirena Vilca, Franz; Guerrero Abad, Juan Carlos; Amasifuen Guerra, Carlos Alberto; Gutierrez Reynoso, Dina Lida; Injante Silva, Pedro Hugo; Arbizu, Carlos I (F1000Research, 2025)
The article is a preprint, it is important to consider that it is not peer-reviewed